Pengaruh Return On Assets (ROA), Leverage Dan Ukuran Perusahaan Terhadap Tax Avoidance - Sekar Utami; Suhono Suhono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to see the effect of Return On Assets (ROA), Leverage, and Company Size on Tax Avoidance in automative sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2012-2018. The population in this study uses 15 sub-manufacturing companies. Automotive sector listed on the Indonesia Stock Exchange. The sample selection technique used in this research is purposive sampling method, and obtained 8 sub-automotive manufacturing companies that meet the requirements as the research sample. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that of the 3 variables tested, 2 were proven to effect tax avoidance, namely the variable ROA, company size. Meanwhile the leverage variable has no effect on tax avoidance. Keywords: Tax Avoidance, Return on Assets, Leverage, Company Size.